Specific Self‐Repairing by Morphology Prejudging. Issue 12 (25th October 2019) - Wang, Pengfei; Li, Mingwei; Hu, Zhitao; Hu, Zhiqiang; Hu, Jinsan
Abstract: The thin surface layer growth during the regeneration of incomplete potassium dihydrogen phosphate crystal is more perplexing than the ordinary layer‐by‐layer growth. In a previous paper, the driving force of the thin surface layer growth was discussed; the present paper focuses on the regeneration process and final regeneration morphology. Based on the analysis of thin surface layer area per unit repaired volume, it is found that convex polyhedron is more advantageous than concave polyhedron. It is also found that the general morphology of repaired incomplete crystal is convex polyhedron of minimum volume covered by singular surfaces. The most important thing is, numbers of regeneration details suggest that the incomplete crystal achieves the self‐repairing by morphology prejudging. Abstract : A series of well‐designed regeneration experiments of potassium dihydrogen phosphate (KDP) crystals with different incomplete shapes show that, based on morphology prejudging, the incomplete crystals all successfully repair themselves to convex polyhedrons of minimum volume by growing thin surface layers of correct type (100 or 101) and precise amount.